3′ Branch ligation: a novel method to ligate non-complementary DNA to recessed or internal 3′OH ends in DNA or RNA. (13th November 2018) - Wang, Lin; Xi, Yang; Zhang, Wenwei; Wang, Weimao; Shen, Hanjie; Wang, Xiaojue; Zhao, Xia; Alexeev, Andrei; Peters, Brock A; Albert, Alayna; Xu, Xu; Ren, Han; et al.
Abstract: Nucleic acid ligases are crucial enzymes that repair breaks in DNA or RNA during synthesis, repair and recombination. Various genomic tools have been developed using the diverse activities of DNA/RNA ligases. Herein, we demonstrate a non-conventional ability of T4 DNA ligase to insert 5′ phosphorylated blunt-end double-stranded DNA to DNA breaks at 3′-recessive ends, gaps, or nicks to form a Y-shaped 3′-branch structure. Therefore, this base pairing-independent ligation is termed 3′-branch ligation (3′BL). In an extensive study of optimal ligation conditions, the presence of 10% PEG-8000 in the ligation buffer significantly increased ligation efficiency to more than 80%. Ligation efficiency was slightly varied between different donor and acceptor sequences. More interestingly, we discovered that T4 DNA ligase efficiently ligated DNA to the 3′-recessed end of RNA, not to that of DNA, in a DNA/RNA hybrid, suggesting a ternary complex formation preference of T4 DNA ligase. These novel properties of T4 DNA ligase can be utilized as a broad molecular technique in many important genomic applications, such as 3′-end labelling by adding a universal sequence; directional tagmentation for NGS library construction that achieve theoretical 100% template usage; and targeted RNA NGS libraries with mitigated structure-based bias and adapter dimer problems.